Proceedings of the 12th ACM Workshop on Artificial Intelligence and Security 2019
DOI: 10.1145/3338501.3357366
|View full text |Cite
|
Sign up to set email alerts
|

Making Targeted Black-box Evasion Attacks Effective and Efficient

Abstract: We investigate how an adversary can optimally use its query budget for targeted evasion attacks against deep neural networks in a blackbox setting. We formalize the problem setting and systematically evaluate what benefits the adversary can gain by using substitute models. We show that there is an exploration-exploitation tradeoff in that query efficiency comes at the cost of effectiveness. We present two new attack strategies for using substitute models and show that they are as effective as previous "query-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…2) Robustness: In practical applications, it has been recently shown that machine learning models are vulnerable to uncertainties (i.e., data outliers and measurement noise) of the input data which may cause misclassification [73]. It is possible to enhance the robustness of machine learning model via robust loss functions, parameter regularization, and reliable optimizers.…”
Section: Research Prospectsmentioning
confidence: 99%
“…2) Robustness: In practical applications, it has been recently shown that machine learning models are vulnerable to uncertainties (i.e., data outliers and measurement noise) of the input data which may cause misclassification [73]. It is possible to enhance the robustness of machine learning model via robust loss functions, parameter regularization, and reliable optimizers.…”
Section: Research Prospectsmentioning
confidence: 99%
“…Previous methods have shown success against a specific set of attack methods and have generally failed to provide complete and generic protection [14]. This field has been spreading rapidly, and, in this field, lots of dangers have attracted increasing attention from escaping the filters of unwanted and phishing e-mails, to poisoning the sensor data of a car or aircraft that drives itself [4,41]. Disaster scenarios can occur if any precautions are not taken in these systems [30].…”
Section: Introductionmentioning
confidence: 99%